ADP‐ribosyltransferases, an update on function and nomenclature. (13th September 2021) - Lüscher, Bernhard; Ahel, Ivan; Altmeyer, Matthias; Ashworth, Alan; Bai, Peter; Chang, Paul; Cohen, Michael; Corda, Daniela; Dantzer, Françoise; Daugherty, Matthew D.; Dawson, Ted M.; Dawson, Valina L.; et al.
Abstract : ADP‐ribosylation, a modification of proteins, nucleic acids, and metabolites, confers broad functions, including roles in stress responses elicited, for example, by DNA damage and viral infection and is involved in intra‐ and extracellular signaling, chromatin and transcriptional regulation, protein biosynthesis, and cell death. ADP‐ribosylation is catalyzed by ADP‐ribosyltransferases (ARTs), which transfer ADP‐ribose from NAD + onto substrates. The modification, which occurs as mono‐ or poly‐ADP‐ribosylation, is reversible due to the action of different ADP‐ribosylhydrolases. Importantly, inhibitors of ARTs are approved or are being developed for clinical use. Moreover, ADP‐ribosylhydrolases are being assessed as therapeutic targets, foremost as antiviral drugs and for oncological indications. Due to the development of novel reagents and major technological advances that allow the study of ADP‐ribosylation in unprecedented detail, an increasing number of cellular processes and pathways are being identified that are regulated by ADP‐ribosylation. In addition, characterization of biochemical and structural aspects of the ARTs and their catalytic activities have expanded our understanding of this protein family. This increased knowledge requires that a common nomenclature be used to describe the relevant enzymes. Therefore, in this viewpoint, we propose an updated and broadly supported nomenclature for mammalian ARTs that will facilitate future discussions when addressing the biochemistry and biology of ADP‐ribosylation. This is combined with a brief description of the main functions of mammalian ARTs to illustrate the increasing diversity of mono‐ and poly‐ADP‐ribose mediated cellular processes. Abstract : ADP‐ribosylation, the transfer of ADP‐ribose from NAD + onto substrates, is catalyzed by proteins with an ADP‐ribosyltransferase (ART) domain. This fully reversible modification can occur as mono‐ or poly‐ADP‐ribosylation. Here, we propose an updated nomenclature for mammalian ARTs and provide a brief description of the main functions of these proteins to illustrate the increasing diversity of the cellular processes that are regulated by mono‐ and poly‐ADP‐ribosylation.